2019
DOI: 10.1038/s41598-019-54648-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly in ultrahigh molecular weight sphere-forming diblock copolymer thin films under strong confinement

Abstract: Ultrahigh molecular weight (UHMW) diblock copolymers (DBCs) have emerged as a promising template for fabricating large-sized nanostructures. Therefore, it is of high significance to systematically study the influence of film thickness and solvent vapor annealing (SVA) on the structure evolution of UHMW DBC thin films. In this work, spin coating of an asymmetric linear UHMW polystyrene-block-poly(methyl methacrylate) (PS-b-PMMA) DBC is used to fabricate thin films, which are spherically structured with an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…[255][256][257][258][259] In Figure 7b (from left to right), a self-assembled spherical structure of PSPI block copolymer dissolved in toluene is reported after a thermal solvent annealing (below 100°C). Cao et al [259] showed a promising way to fabricate large-sized nanostructures, investigating the influence of the spin coating parameters and solvent vapor annealing on the self-assembly of multi-geometrical ordered structure. Further, Jacucci et al [260] investigated the optimization of the morphology of the scatterer elements rather than the tunability of their refractive index, obtaining silica-based spheroid-cylindrical particles as colloids, thus showing a new class of pigment microsphere for ultrabright coatings.…”
Section: Leucophore As Incoherent Structural Scatterersmentioning
confidence: 99%
See 1 more Smart Citation
“…[255][256][257][258][259] In Figure 7b (from left to right), a self-assembled spherical structure of PSPI block copolymer dissolved in toluene is reported after a thermal solvent annealing (below 100°C). Cao et al [259] showed a promising way to fabricate large-sized nanostructures, investigating the influence of the spin coating parameters and solvent vapor annealing on the self-assembly of multi-geometrical ordered structure. Further, Jacucci et al [260] investigated the optimization of the morphology of the scatterer elements rather than the tunability of their refractive index, obtaining silica-based spheroid-cylindrical particles as colloids, thus showing a new class of pigment microsphere for ultrabright coatings.…”
Section: Leucophore As Incoherent Structural Scatterersmentioning
confidence: 99%
“…For example, di-block copolymers show photonic bandgap in the visible range thanks to self-assembled ordered nanostructures. [255][256][257][258][259] In Figure 7b (from left to right), a self-assembled spherical structure of PSPI block copolymer dissolved in toluene is reported after a thermal solvent annealing (below 100°C). Cao et al [259] showed a promising way to fabricate large-sized nanostructures, investigating the influence of the spin coating parameters and solvent vapor annealing on the self-assembly of multi-geometrical ordered structure.…”
Section: Leucophore As Incoherent Structural Scatterersmentioning
confidence: 99%
“…ii) The complex molecular topology and conformation of LBCPs in solvent can cause slow self-assembly dynamics. [5,6,95,96] An alternative class of BCP, the brush block copolymer (BBCP), also known as a bottlebrush block copolymer or molecular brush, promises to alleviate these issues, allowing for greater access to photonic materials. BBCPs have densely grafted side chains and the strong steric hindrance of these side chains significantly increases the rigidity of the polymer backbone, which extends the conformation of the BBCP and reduces chain entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…SVA involves the uptake of solvent into a BCP film, resulting in increased polymer chain mobility, a lower effective value of T g , and the avoidance of any thermal degradation of the material. There are multiple interdependent variables that influence the SVA process, including pressure, temperature, and humidity. Nonetheless, previous work has shown that it can be performed with a very simple strategy known as “static” SVAthis consists of a BCP sample placed inside a sealed chamber containing a reservoir of solvent, which is then left for a predetermined period of time. Moreover, SVA can be performed at room temperatures or below and has been proven to effectively induce self-assembly in a number of UHMW BCP systems. , Kim et al successfully obtained phase separation of lamellar and gyroid UHMW polystyrene- block -poly­(methyl methacrylate) (PS- b -PMMA) BCP films with periods of ∼200 nm using tetrahydrofuran (THF) as a neutral solvent for SVA, followed by a 12 h thermal annealing step. , Phase separation of a UHMW spherical PS- b -PMMA system was also demonstrated by Cao et al again using THF as the annealing solvent of choice . Additionally, Takano et al developed a novel instrumentation technique to monitor the phase separation of UHMW lamellar PS- b -PMMA using in situ atomic force microscopy (AFM) under high swelling conditions during SVA .…”
Section: Introductionmentioning
confidence: 99%
“…achieved the phase separation of a high molecular weight PS-P2VP system ( M n = 430 kg/mol) in a time period of 1 h using an uncontrolled “static” SVA strategy . Despite the relative success of these previous studies for the induction of phase separation in UHMW systems, the required timescales often extended from several hours to daysthereby severely hindering the industrial applicability of such processes. , The acceleration of the SVA process is therefore critical for the future development of this field. Here, we demonstrate a procedure for ultrafast self-assembly of UHMW BCP systems by controlling the swelling kinetics during SVA, reducing the required annealing time to minutes.…”
Section: Introductionmentioning
confidence: 99%